Prevalence and Clindamycin Resistance Profile of Staphylococcus aureus and Associated Factors among Patients Attending the University of Gondar Comprehensive Specialized Hospital, Gondar, Northwest Ethiopia - Ambachew, Aklilu; Gebrecherkos, Teklay; Ayalew, Getnet (Interdisciplinary Perspectives on Infectious Diseases, 2022)
Clindamycin can serve as an alternative treatment for staphylococcal infections. Routine susceptibility tests may fail to determine inducible type clindamycin resistance and can be a source of failure in clinical therapeutics. Therefore, this study aimed to determine Staphylococcus aureus (S. aureus) prevalence, inducible clindamycin resistance pattern, and associated factors among patients attending the University of Gondar Comprehensive Specialized Hospital, Gondar, northwest Ethiopia. Methods. A cross-sectional study was conducted from January to April 2018. Clinical samples were inoculated on appropriate culture media. Standard bacteriological tests, including Gram stain, catalase, and coagulase tests, identified the presence of S. aureus. The antimicrobial susceptibility tests and the D-test were performed by using the Kirby–Bauer disk diffusion technique on the Mueller–Hinton agar. The D-test was performed using clindamycin (CLI) 2 ug and erythromycin (ERY) 15 ug disks located approximately 15 mm apart, and the cefoxitin susceptibility test was used to characterize methicillin-resistant S. aureus (MRSA). The association between S. aureus infection and different variables was assessed using bivariate and multivariate analysis. A P value <0.05 was considered statistically significant. Result. Of 388 study participants, the overall prevalence of S. aureus was 17% (66/388). Of these, the inducible type of clindamycin resistance was 25.8% (17/66) and 21.2% (14/66) were MRSA. All isolates were susceptible to chloramphenicol and resistant to tetracycline. A family size of 4–6 (AOR = 2.627, 95% CI (1.030–6.702)) and >7 (AOR = 3.892, 95% CI (1.169–12.959)), inpatient study participants (AOR = 3.198, 95% CI (1.197–8.070)), illness in the previous 4 weeks (AOR = 2.116, 95% CI (1.080–4.145)), and a history of chronic disease (AOR = 0.265, 95% CI (0.094–0.750)) were likely to have S. aureus infection. Conclusion. This study shows a considerable high magnitude of MRSA and inducible clindamycin resistance S. aureus isolates. To rule out clindamycin susceptibility testing, the D-test should be routinely performed.